Effect of integrated non-pharmacological therapy on second-stage labor duration and neonatal Apgar scores - Rosmiarti,; Marlin, Riska; Bahriah , Yuli (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2026)
Background: Childbirth is a physiological process influenced by maternal physical and psychological conditions. A prolonged second stage of labor is associated with increased risks of maternal fatigue, birth canal trauma, and impaired neonatal adaptation. However, evidence regarding structured integrated non-pharmacological interventions during labor remains limited. Purpose: This study aimed to evaluate the effect of an integrated non-pharmacological intervention on second-stage labor duration and neonatal Apgar scores. Methods: A quasi-experimental study was conducted from January to June 2025 among 60 women with term singleton pregnancies (intervention, n = 30; control, n = 30). Participants were allocated consecutively into two groups. The intervention consisted of Qur’anic recitation, cold compress application, and effleurage massage. The primary outcome was second-stage labor duration, and secondary outcomes were Apgar scores at 1 and 5 minutes after birth. Data were analyzed using independent t-tests and regression analysis, with a significance level of p < 0.05. Results: The intervention group had a significantly shorter second-stage labor duration than the control group (mean difference = −14.4 minutes; 95% CI: −19.2 to −9.6; p < 0.001). Neonates in the intervention group had significantly higher Apgar scores at 1 minute (mean difference = 0.8; 95% CI: 0.41 to 1.19; p = 0.002) and 5 minutes (mean difference = 0.6; 95% CI: 0.32 to 0.88; p = 0.001). Conclusions: An integrated non-pharmacological intervention was associated with shorter second-stage labor duration and higher early neonatal Apgar scores. This multimodal approach may provide a feasible, low-cost supportive strategy for intrapartum care in low-resource settings. Further randomized controlled trials are warranted to confirm these findings.